Neighbors, Nørgaard & Woodacre, Notions of Privacy at Early Modern European Courts. Reassessing the Public and Private Divide, 1400-1800 (Amsterdam University Press, 2024) - Sanne Maekelberg (Royal Studies Journal)
Review of Dustin M. Neighbors, Lars Cyril Nørgaard & Elena Woodacre, Notions of Privacy at Early Modern European Courts. Reassessing the Public and Private Divide, 1400-1800 (Amsterdam: Amsterdam University Press, 2024)